2013
DOI: 10.1111/dsu.12081
|View full text |Cite
|
Sign up to set email alerts
|

Superficial Hemangioma: Pulsed Dye Laser Versus Wait-and-See

Abstract: Pulsed dye laser is only to be considered as an alternative treatment up to the age of 6 months, at which time parents and physicians consider cosmetic outcome to be a relevant factor, but laser therapy plays a major role in the treatment of residual lesions at older ages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
2
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 35 publications
(70 reference statements)
3
47
2
5
Order By: Relevance
“…Recently, PDL has been used in the treatment of SH. Our result and other reviews discussing the pros and contras of early laser treatment of hemangioma confirmed that in the treatment of SH, the 595 nm PDL is the treatment of excellent choice (15). SH may be treated safely and effectively with the PDL in the early days of life due to accelerated remission and resolution.…”
Section: Effective Rate Affected By Occurrence Timesupporting
confidence: 78%
“…Recently, PDL has been used in the treatment of SH. Our result and other reviews discussing the pros and contras of early laser treatment of hemangioma confirmed that in the treatment of SH, the 595 nm PDL is the treatment of excellent choice (15). SH may be treated safely and effectively with the PDL in the early days of life due to accelerated remission and resolution.…”
Section: Effective Rate Affected By Occurrence Timesupporting
confidence: 78%
“…However, the cosmetic outcome was significantly better in the PDL group. [62] In a comparative study between traditional PDL (585 nm) and long PDL (LPDL; 595 nm), the authors found that a similar number of infants achieved complete clearance or showed minimal residual signs at 1 year of age (14/26, 54% in PDL group vs. 17/26, 65% in LPDL group; P = 0.4), although the infants in LPDL group suffered significantly less side-effects like hypo- or hyperpigmentation, textural changes and the period of maximal proliferation was also significantly shortened (106 days in LPDL versus 177 days in PDL group). [63]…”
Section: Topical Therapymentioning
confidence: 99%
“…Instead of waiting passively for natural regression that may take a long time and even lead to suboptimal cosmetic results and psychosocial distress despite later intervention, the high safety profile of topical timolol and/or PDL presents a splendid opportunity to actively intervene early, safely, and nonsystemically with a higher likelihood of earlier and complete regression [10,12,[27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…The 595 nm pulse dye laser (PDL) is another effective treatment for hemangiomas [9][10][11][12]. Patients treated with PDL have evidence of wound healing demonstrable by electron microscopy [13].…”
Section: Introductionmentioning
confidence: 99%